Critical analysis on the choice of Takaful (Islamic insurance) operating models in Malaysia - Htay, Sheila Nu Nu; Zaharin, Hanna Rabittah (World Business Institute, 2012)
Takaful and insurance have been compared long ago by many scholars around the world. Prior literatures of Takaful are mainly focusing on the concept and theoretical nature of takaful and its differences from insurance. Malaysian Takaful industry has been given flexibility in terms of the operational models adopted and to the researchers’ knowledge; no research has been conducted in Malaysia regarding the choice of Takaful operational models by Takaful operators. It is important to study the motives behind choosing among different Takaful models since different models have different impacts on the surplus distribution of Takaful funds, especially for Family Takaful funds. Therefore, this research is conducted to examine on reasons behind choosing Takaful models and to propose the most suitable model to be adopted by Takaful operators to be fair and equitable for both Takaful operators and participants. The representatives from Takaful operators are interviewed and it has been found out that most of Takaful operators prefer the Hybrid Wakalah or Modified Wakalah (principal-agent) model. The main reason is that Central Bank of Malaysia clearly sets the rule that in the Wakalah contract; Takaful operators can charge Wakalah fess (agent fees and administrative expenses) upfront to the participants (certificate holders). Moreover, an upper limit Wakalah fees is 40% and hence, it is favorable to Takaful operators. The mudarabah (profit and loss sharing) model is not much favored in the Malaysian Takaful industry due to its profit sharing nature which strains the Takaful Operators to purely claim the profit out of the actual performance of the profit. Interview results further find out that most of the practitioners also think that the Wakalah fees imposed on the participants are too much and the Hybrid Wakalah/ Modified Wakalah model has too many layers of charging profits from the funds and consequently, the currently adopted models are at the disadvantages of participants. Since this research provides a clear picture of the current practice of the Family Takaful operating models adopted by the Malaysian Takaful operators, these findings will be useful for regulators and shari’ah advisors to look into this issue again to be fair and justice to involved parties.